Lithological Prediction in Elastic Impedance Domain - Chow, Weng Sum (2012)
Prediction of lithology in subsurface usually is a complex problem. Amplitude versus Offset (AVO) and Extended Elastic Impedance (EEI) rotation can predict the petrophysical properties hence reduce the ambiguity in lithology prediction. This study will implement the AVO and EEI rotation concept to construct seismic equivalent of petrophysical properties. The spectral blueing and colored inversion will be applied into this seismic equivalent to improve the lithology prediction. This work start by EEI log derivation from density and velocity logs, the shear velocity is estimated using Greenberg Castagna, then the EEI log are correlated with GR log to calculate the optimum rotation angle. Intercept and gradient of AVO are calculated from seismic volume and EEI equivalent for lithological prediction is constructed by rotating intercept and gradient with optimum rotation angle which obtained from previous step. The spectral blueing is then applied into EEI equivalent to increase frequency content. Finally, elastic impedance are obtained by inverted the seismic volume using colored inversion. Our application shows that the lithological properties can be interpreted from equivalent seismic volume in the elastic domain. Rotation of AVO response on certain optimum angles can help the petrophysical properties prediction in the zone interest of reservoir. The best correlation between EEI log with GR occurs at 33.8 degrees. Implementation of spectral blueing technique on this lithology reflectivity equivalent successfully improved the seismic resolution. Consequently, several thin sand targets and top/on lap structure can be seen clearly.